Hybrid nanocomposites for nanotechnology : electronic, optical, magnetic and biomedical applications - Merhari, Lhadi (Springer, 2017)
Hybrid Nanocomposites for Nanotechnology: Electronic, Optical, Magnetic and Biomedical Applications introduces readers to the complex development of new functional organic-inorganic nanomaterials and explores their non-traditional applications. The traditional application of these nanocomposites has been the reinforcement of plastics by the addition of inorganic fillers, exploiting the enhancement of mechanical properties for commodity plastics. Hybrid nanocomposites provide an attractive, versatile, technological platform for emerging high-added-value applications such as photovoltaic cells and light-emitting devices, lithium-ion batteries, supercapacitors, and biosensors.